2022
DOI: 10.1016/j.scs.2021.103430
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Computational Intelligence Algorithm for Autonomous Handling of COVID-19 Pandemic Emergency in Smart Cities

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…An analysis of COVID-19 using an intelligent framework to help healthcare teams make rapid decisions in hospitals, in terms of quarantine, identifying and treating patients with a typical cold has been studied by Abdel-Basset, Chang, and Nabeeh [8]. The study proposed a hybrid Computational Intelligent Algorithm (CI) using Moth-Flame Optimization and Marine Predators Algorithms (MOMPA) to detect the shortest path to the emergency location of COVID-19 without direct interaction with other subjects [18]. Several studies related to reducing the risk of COVID-19 transmission via swabbing through the use of IoT and intelligent frameworks were also conducted [19], [22].…”
Section: Intelligent Framework Innovationmentioning
confidence: 99%
“…An analysis of COVID-19 using an intelligent framework to help healthcare teams make rapid decisions in hospitals, in terms of quarantine, identifying and treating patients with a typical cold has been studied by Abdel-Basset, Chang, and Nabeeh [8]. The study proposed a hybrid Computational Intelligent Algorithm (CI) using Moth-Flame Optimization and Marine Predators Algorithms (MOMPA) to detect the shortest path to the emergency location of COVID-19 without direct interaction with other subjects [18]. Several studies related to reducing the risk of COVID-19 transmission via swabbing through the use of IoT and intelligent frameworks were also conducted [19], [22].…”
Section: Intelligent Framework Innovationmentioning
confidence: 99%
“…Los sensores de naturaleza ubicua conectados a internet (internet de las cosas) en las ciudades inteligentes con fines analíticos que son procesados con algoritmos (ejemplo redes neuronales y árboles de decisiones entre los más simples) con mínima participación humana derivan en patrones que permiten a las autoridades sanitarias apoyar la lucha contra la infección por SARS-CoV-2 (por ejemplo tendencias de la atención médica, atención en los servicios de salud, asociaciones de riesgo y predicción de resultados), pues adoptarían las mejores estrategias para combatir la enfermedad en tiempo real (limitación de la propagación, pronóstico de epidemias, diagnósticos de casos, seguimiento de pacientes con la enfermedad, rastreo de pacientes potenciales, sugerencias de métodos para el desarrollo de vacunas, el descubrimiento de fármacos) (Lagos et al, 2020;Absalom et al, 2021;Adil & Khan, 2021;El Azzaoui et al, 2021;Manimuthu et al, 2021;Saponara et al, 2021;Umair et al, 2021;Abdel-Basset et al, 2022).…”
Section: Generalidades Que Describen a Las Ciudades Inteligentes Y Pe...unclassified
“…The literature review showed that a great many studies concern integrating the IoT with WSN technologies for smarter city projects. There is a particular emphasis on how these technologies can improve efficiency and sustainability in urban areas of all kinds, not just traffic management problems [12], [13]. Traffic management is one of the key areas of focus for smart city research.…”
Section: Introductionmentioning
confidence: 99%